“Isn’t She Painted Con Amore?” Fraser’s Magazine and the Spectacle of Female Genius - Higgins, David (Romanticism on the Net, 2007)
AbstractDuring the Romantic period, it became possible to transform authorship into celebrity through a process of what might be termed ‘spectacularisation’. Verbal and visual representations of certain writers as private individuals, which often appeared in the periodical press, helped to mark them out within a massively competitive literary marketplace and provided their readers with a sense of intimate connection. This article considers this process in relationship to the women writers depicted in William Maginn’s “Gallery of Illustrious Literary Characters” (Fraser’s Magazine, 1830-36). In particular, I argue that the 1836 article ‘Regina’s Maids of Honour’ is crucial for understanding not only how the “Gallery’s” mixed rhetoric of chivalry and prurience operates both to restrict and expose its female subjects, but also Maginn’s intense self-consciousness about this process. Throughout, he conflates references to his subjects’ works with descriptions of their looks, thereby ensuring that their public lives as writers cannot be separated from the inspection of their bodies by a masculine observer. Although “Regina’s Maids of Honour” places women writers in a genteel domestic setting, Maginn offers male readers a frisson of scandalous excitement with sexualized portrayals of those – Caroline Norton, Letitia Landon, and Marguerite Blessington – whose lifestyles challenged the strict boundaries of domestic propriety.